The Challenge of Measuring Financial Impacts From Investments in Corporate Social Performance - Peloza, John (Journal of management, 2009)
There is a small, but positive, relationship between corporate social performance and company financial performance. However, research in this area has provided little guidance to managers on how they should measure the financial impacts of their CSP strategies. Commonly used market measures, such as share price, or accounting measures, such as return on equity, are impacted by a host of other variables. These metrics do not provide the necessary level of detail for managers who want to establish an optimal level of CSP investment for their company. Further, academic research has tended to overlook the mediation process between CSP and financial performance. This gap limits the practical application of research and leaves the question of causality unaddressed. The author reviews the research examining the business case for CSP from both the academic and practitioner literatures, and provide recommendations for managers interested in measuring the impacts of CSP investment on financial performance.